Effect of Copper and Silicon on the Corrosion Properties of the AlCrFeMnNi High Entropy Alloy - Tripathy R.R.; Shadangi Y.; Pradhan P.; Mukherjee B.; Raja V.S.; Mukhopadhyay N.K. (My University, 2025)
Microstructural and electrochemical corrosion behaviours of Al40(SiCrFeMnNiCu)60 (at %) high entropy alloy (HEA) were studied. The as-cast-alloy formed B2 and Cr5Si3 intermetallic phases. The HEA showed active, passive and transpassive behaviour for pH (0–3), and spontaneous passivity for pH (14–11). The HEA showed higher transpassive dissolution at low pH values than alkaline pH values. This has been attributed to minor variation in the passive film composition of the HEA between the acidic and alkaline pH condition as observed using X–ray photoelectron spectroscopy (XPS). Considering the beneficial role of copper and silicon in sulphuric acid in stabilizing the passive film in reducing the critical current density for passivation and also the role of silicon in stabilizing the passive film, they are suggested to be responsible for the improved passivity. In 3.5 wt% NaCl solution, the alloy did not show any kind of passivity. The selective dissolution of the alloy was evident at B2/Cr5Si3 interface regions and the Cr5Si3 phase showed relatively more resistance to corrosion. © The Indian Institute of Metals - IIM 2024.